Geriatric competencies, teaching modality and ageism in medical students in the context of the COVID-19 pandemic - Zambrano Monzón, Martín Adrián (2022)
Introduction. The current COVID-19 pandemic has forced medical education to change to a virtual modality. This can influence the quality of teaching and the perception that students have about older adults. Objective. Our objective is to evaluate the perception of the self-report fulfillment of geriatric competencies (SRFGC) in medical students from universities in Lima-Peru, comparing face-to-face and virtual techniques. Methods. A cross-sectional study was designed including students from 3 universities in Lima, Peru who have taken the geriatrics course in person or virtually, measuring the main variables such as ACCG according to the recommendations of the pogoe web portal and ageing the UCLA-GAS scale. Averages and standard deviations were calculated for numerical variables and frequency for categorical variables. Bivariate analysis was also performed between ACCG and the rest of the variables measured. Results. Means 0.72 (SD=0.22) were found for the face-to-face modality and 0.75 (SD=0.23) for virtual teaching. We found no statistical association between the study variables (p value = 0.39), so there is no difference between the SRFGC between the virtual and face-to-face modalities. Through a linear regression model of SRFGC and ageism adjusted to statistically significant variables of the study, it was found that the greater the SRFGC, the greater the ageism. Conclusions. So far, it cannot be said that virtual education is inferior to face-to-face education with regard to the SRFGC.